2020
DOI: 10.1002/ajim.23164
|View full text |Cite
|
Sign up to set email alerts
|

Should public safety shift workers be allowed to nap while on duty?

Abstract: Fatigue and sleep deficiency among public safety personnel are threats to wellness, public and personal safety, and workforce retention. Napping strategies may reduce work‐related fatigue, improve safety and health, yet in some public safety organizations it is discouraged or prohibited. Our aim with this commentary is to define intra‐shift napping, summarize arguments for and against it, and to outline potential applications of this important fatigue mitigation strategy supported by evidence. We focus our dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 83 publications
0
8
1
Order By: Relevance
“…Next, the officers in this study reported that napping was not helpful in alleviating their fatigue during the shift. This is somewhat contrary to previous research on the benefits of napping (e.g., Martin-Gill et al, 2018; Patterson et al, 2020). We speculate that this difference may result from times when officers in this study took their naps; they tended to nap only when they were very tired and thus likely to go into deep sleep at a faster rate.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Next, the officers in this study reported that napping was not helpful in alleviating their fatigue during the shift. This is somewhat contrary to previous research on the benefits of napping (e.g., Martin-Gill et al, 2018; Patterson et al, 2020). We speculate that this difference may result from times when officers in this study took their naps; they tended to nap only when they were very tired and thus likely to go into deep sleep at a faster rate.…”
Section: Discussioncontrasting
confidence: 99%
“…We speculate that this difference may result from times when officers in this study took their naps; they tended to nap only when they were very tired and thus likely to go into deep sleep at a faster rate. Previous reviews on short naps (Hilditch et al, 2017; Patterson et al, 2020) acknowledged that individuals waking from deep sleep typically experience sleep inertia, which is a state of grogginess experienced upon waking. Sleep inertia tends to require more effort to achieve wakefulness and can adversely impact post-waking performance for up to 15 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…However, though the importance of the fixed-loading method is indisputable, it also has some disadvantages. For instance, due to the diurnal variation of the physiological index, the maximum strength can change up to 10-20% (Poliquin, 1988), and other factors can also affect the sports performance, such as sleeping conditions, warmup programs, and sports supplements intake (Warren et al, 2009;Amiri-Khorasani and René, 2014;de Salles Painelli et al, 2014;Baxter et al, 2016;Abbott et al, 2020;Patterson et al, 2020), which makes it very hard to choose an appropriate working load according to an athlete's body condition (Kraemer and Fleck, 2007), thus the longterm development of strength is limited. Consequently, the uncertainties in training may result in overtraining or inadequate training, and followed by injury or degeneration in training (Poliquin, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The first qualitative interview following commencement of shift work (Time 1) will ask interns to recall their experience of sleep inertia and whether they have had any education regarding sleep inertia ( S4 Appendix ). Finally, all interviews from commencement of shift work (Time 1) will ask interns about their experience of napping, sleep inertia and performance on night shift which existing literature suggests may influence recovery and sleep in paramedics [ 47 ] ( S5 Appendix ). Further, interns will be asked to describe any strategies they use to combat sleep inertia to further understand countermeasures for the decline in performance upon waking associated with sleep inertia [ 48 ].…”
Section: Study Proceduresmentioning
confidence: 99%